Membangun Keluarga Sejahtera melalui Sosialisasi Perencanaan Keuangan Rumah Tangga dan Investasi Bijak - Frem, Marianus Alfan; Navo, Andreas Hariyano; Wongsono, Briand Christofer; Helmon, Kristoforus Eugenius Crisen; Beribe, Veren Brigitha; Mau, Januaria Benga; Obe, Regina; Penu, Elfrida Cindi; Koy, Karina Ristanti S.; Jafrisma, Apolonia; Bouk, Kornelia Bete; Awang, Rambu Marshanda; Rekong, Karolina; Riwu, Elda E. J.; Pratama, Maria Nindri Saputri; Cipriano, Epifania Angelika; Mau, Ignatia Thomasita Bau; Seran, Paskalis; Manafe, Henny; Man, Stanis (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The main objective of this activity was to improve the financial literacy of the village community, particularly in terms of household financial planning and understanding wise investment. Field observations indicate that most residents are unfamiliar with creating a household budget, tend to be consumptive, and lack an understanding of legal and safe forms of investment. The outreach activities, which included material delivery, discussions, and simple record-keeping practices, successfully improved participants' understanding, as demonstrated by an increase in post-test scores compared to the pre-test. Furthermore, new solutions offered in this activity included the implementation of micro-savings, simple diary-based financial record-keeping, the use of village cooperatives as a means of collective investment, and an introduction to simple digital financial literacy. These findings align with various previous studies emphasizing the importance of financial literacy in family financial management. Therefore, this community service activity not only improves understanding but also provides practical strategies that communities can implement to build household economic independence and avoid the risk of fraudulent investments.